Implementasi Good Governance dalam Pelayanan Kependudukan Digital di Kecamatan Medan Marelan dalam Hukum Administrasi Negara - Nuraini Nuraini; Muhammad Syukran Yamin Lubis (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
This study aims to analyze the implementation of good governance principles in digital population administration services in Medan Marelan Subdistrict from the perspective of Administrative Law. The background of this research is based on the importance of digital transformation in public services through the Electronic-Based Government System (SPBE) to enhance transparency, accountability, effectiveness, and efficiency. However, in practice, several obstacles are still encountered, such as limited infrastructure, network disruptions, and limited human resources. This research employs an empirical legal research method with both empirical and statutory approaches. Data were collected through field research, including interviews with subdistrict officials and the community, as well as library research involving laws, regulations, and relevant literature. The data were analyzed qualitatively to examine the conformity between the implementation of services and the principles of good governance and general principles of good administration (AUPB). The results show that the implementation of good governance principles in digital population services in Medan Marelan Subdistrict has not been fully optimal. This is indicated by challenges in information transparency, system effectiveness, and limitations in human resources and infrastructure. Nevertheless, digital services have provided convenience for the community in accessing population administration services. In conclusion, improvements in human resources quality, technological infrastructure, and the strengthening of supervision and evaluation mechanisms are necessary to achieve public services that align with good governance principles.